Ocular Characteristics of Patients with Leber Congenital Amaurosis 6 Caused by Pathogenic RPGRIP1 Gene Variation in a Chinese Cohort - Yumei Mao; Yanling Long; Bo Liu; Qingling Cao; Yijian Li; Sha Li; Gang Wang; Xiaohong Meng; Shiying Li (Journal of Ophthalmology)
Purpose. To delineate the clinical and genetic characteristics of Chinese patients with RPGRIP1-associated Leber congenital amaurosis 6 (LCA6). Methods. After screening 352 unrelated families with clinically diagnosed RP, five LCA6 patients with RPGRIP1 variations from unrelated Chinese families were identified. Full ophthalmology examinations, including decimal best-corrected visual acuity (BCVA), fundus photography, fundus autofluorescence imaging, spectral-domain optical coherence tomography (SD-OCT), full-field electroretinography (ffERG), multifocal electroretinography (mfERG), perimetry, and flash visual evoked potential (FVEP), were performed. Target next-generation sequencing (NGS) and Sanger sequencing were performed for the five patients to identify and to validate candidate disease-causing variants. Results. Five patients were molecularly diagnosed as the LCA6 associated with RPGRIP1 variation, with typical clinical characteristics including congenital night blindness, nystagmus, and visual defect, at an early age. Interestingly, LCA6 exhibited extensive clinical heterogeneity and the changes in the morphology and function were not completely consistent in the five LCA6 patients. Case 1 showed extensive inferior-nasal retinal atrophy with a corresponding area of hypofluorescence in fundus autofluorescence, and the fundus photograph was nearly normal in cases 2 and 3. The ERG results displayed a moderately reduced rod-system response in cases 1 and 2 and a significant reduced rod-system response in case 3. Both case 4 and case 5 showed mottled pigmentation in fundi and an unrecordable rod and cone-system response in ERG. Moreover, we identified eight compound variants and one homozygous variant in the five patients with RPGRIP1. Conclusions. This is the largest report focused on the clinical electrophysiological features of patients with associated LCA6 caused by the variation in the RPGRIP1 gene in the Chinese population with an enriched phenotypic and genotypic background of LCA6 to improve future gene therapies.